Analysis randomness properties of basic components of SNOW 3G cipher in mobile systems - Jassim, Khalid Fadhil; Alshaikhli, Imad Fakhri Taha (IIUM Press, 2016)
SNOW 3G is a stream cipher algorithm used as encryption algorithm in third generation mobile phone technology (3G-UMTS). In this paper, we analyzed and evaluated the randomness properties of basic components of SNOW 3G cipher. NIST test suit (SP 800-22) is used in evaluating and testing the randomness properties. We conducted statistical tests on various components of SNOW 3G cipher such as keystream, Finite State Machine, S-boxes S1 and S2, registers (R1, R2, and R3), and Linear Feedback Shift Register. Our experimental results and empirical analysis shown that SNOW 3G cipher passed statistical randomness tests.